The whole versus the sum of some of the parts: toward resolving the apparent controversy of clitoral versus vaginal orgasms. (1st January 2016) - Pfaus, James G.; Quintana, Gonzalo R.; Mac Cionnaith, Conall; Parada, Mayte
Abstract : Background: The nature of a woman's orgasm has been a source of scientific, political, and cultural debate for over a century. Since the Victorian era, the pendulum has swung from the vagina to the clitoris, and to some extent back again, with the current debate stuck over whether internal sensory structures exist in the vagina that could account for orgasms based largely on their stimulation, or whether stimulation of the external glans clitoris is always necessary for orgasm. Method: We review the history of the clitoral versus vaginal orgasm debate as it has evolved with conflicting ideas and data from psychiatry and psychoanalysis, epidemiology, evolutionary theory, feminist political theory, physiology, and finally neuroscience. Results: A new synthesis is presented that acknowledges the enormous potential women have to experience orgasms from one or more sources of sensory input, including the external clitoral glans, internal region around the "G-spot" that corresponds to the internal clitoral bulbs, the cervix, as well as sensory stimulation of non-genital areas such as the nipples. Conclusions: With experience, stimulation of one or all of these triggering zones are integrated into a "whole" set of sensory inputs, movements, body positions, autonomic arousal, and partner- and contextual-related cues, that reliably induces pleasure and orgasm during masturbation and copulation. The process of integration is iterative and can change across the lifespan with new experiences of orgasm.